Competence of Professional Language Teachers in Providing Educational Services to Improve Students’ Retention Ability - Abdalla Madyen; Mansour Ellafi; Mohammed Elhouni (Universitas Muhammadiyah Barru, 2022)
The current research investigates how professional language teachers’ educational services improve the retention ability for high school students. The population in this study are 635 students of Al Manara School, located at city of Sirte, with 65 students as the sample taken with proportional random sampling technique, and involved two language teachers from the same school, an English teacher and an Arabic teacher. To collect research data, researchers used questionnaire and interview. The data was analyzed using a simple regression formula. The data with a simple regression model with a significance level of the regression was matched with the significance test rules. The result of data analysis indicates that the competence of professional language teachers in educating has a significant effect on increasing students’ memory toward lessons. In addition, the researchers found that there are three pillars of educational services applied by language teachers in educating students. Therefore, it can be concluded that if the professional language teacher education services in educating are improved, there will be an increase in students’ retention ability toward lesson materials.